FAKTOR – FAKTOR PENDORONG PERAN AKTIF INDONESIA DALAM KERJASAMA CORAL TRIANGLE INITIATIVE ON CORAL REEFS, FISHERIES AND FOOD SECURITY (CTI-CFF) TAHUN 2006-2014 - Irayani, Ni Luh Ketut Ayu; Fasisaka, Idin; Parameswari, Anak Agung Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2017)
ABSTRACT Coral triangle area is one of the centre world biodiversity. The region served as source of livelihood, coastal organism breeds location, and also contribute in address global warming issue. However, the coral triangle area, experienced severe damages caused by destructives human activity . Refers to the currents circumstance, Indonesia call for collective engagement to save the biodiversity in the region. The efforts finally resulted in the form of cooperation Coral Triangle Initiative on Coral Reefs Fisheries and Food Security (CTI-CFF) by the six member of CT6. Indonesia persistently make the CTI-CFF as fundamental building block for well established cooperation amongst state member in the region. This research would like to analyse the factor that triggered active role involvement by the Indonesia government in the CTI–CFF. There are several concept to be used in this research, such as rational model actor and internal-external factor. Key Words : Coral Triangle Initiative, CTI–CFF, Rational Actor Model, Internal-External Factor.